Microcomposites of poly(ε-caprolactone) and poly(methyl methacrylate) prepared by suspension polymerization in the presence of poly(ε-caprolactone) macromonomer - Abraham, Gustavo Abel (2002)
Poly(methyl methacrylate)-poly(ε-caprolactone) (PMMA/PCL) microparticles were synthesized by suspension polymerization of methyl methacrylate in the presence of PCL. The incorporation of a small amount of a macromonomer, methacryloyl-terminated PCL (M-PCL), into the reaction mixture, led to the formation of grafted systems, namely PMMA-g-PCL/PCL. The synthesis of the macromonomer and its characterization by nuclear magnetic spectroscopy (1H NMR) is described. The role of M-PCL as an effective compatibilizing agent in the composite was investigated. PMMA/PCL and PMMA-g-PCL/PCL composites were fully characterized by 1H NMR, gel permeation chromatography (GPC) and thermal analysis, including thermogravimetric, analysis (TGA), conventional differential scanning calorimetry (DSC), modulated DSC (MDSC) and dynamic mechanical thermal analysis (DMTA). Finally, the morphology of the prepared systems was investigated by scanning electron microscopy (SEM). The addition of compatibilizing agent led the formation of a more homogeneous microcomposite with improved mechanical properties.